Earnings Inequality and Risk over Two Decades of Economic Development in Lithuania - Jose Garcia-Louzao; Linas Tarasonis (CESifo GmbH, 2025)
Using Social Security records between 2000 and 2020, we provide a comprehensive analysis of labor earnings inequality and its dynamics over the course of Lithuania's economic development. Since 2000, there has been a substantial decline in earnings inequality, largely driven by the rapid growth of earnings at the bottom of the distribution, while earnings volatility has hardly changed. Importantly, we estimate a relatively high sensitivity of earnings growth to changes in real GDP, which declines with the level of permanent income. Additionally, we find that the idiosyncratic earnings risk of individuals at the bottom of the permanent income distribution is less sensitive to aggregate growth than that of individuals in the top half. Taken together, our findings underscore that analyzing earnings risk is critical to properly understanding the dynamics of inequality and designing effective policies to address it.
Keywords: D31; E24; J31; 330; income inequality; income risk; income mobility; administrative data